An ethnographic case study of undergraduate researchers in natural hazards engineering - Amina Meselhe; Karina I. Vielma; Karina I. Vielma; Karina I. Vielma; Karina I. Vielma; Daleen Torres Burgos; Tyler Rodrigues (Frontiers in Built Environment)
Engineering education utilizes various methods to broaden participation in engineering disciplines. Quantitative studies show the demographics and contributing factors of successful engineering researchers within educational pathways. However, there is a need to report on the rich experiences of students who participate in programs designed to prepare undergraduate students to remain and succeed in engineering fields. The paper explores the process and impact of the National Science Foundation (NSF) funded Natural Hazards Engineering Research Infrastructure (NHERI) Research Experience for Undergraduates (REU) using qualitative measures. A humanizing model of the undergraduate researchers as holders of knowledge framed their 10 week research program and associated research opportunities, faculty mentoring, and incorporation into the community of the natural hazards field. The focus of this case study highlighted autoethnographic reflections of REU participants who continued as researchers at various academic institutions or in industry. Led by the students as co-authors, light is shed on their 1) individual professional and personal developments during the process, 2) relationships with peers and mentors, and 3) the career impacts following the experience. This collection of guided reflective responses provide insight into the experiences, merits, and challenges of the undergraduate researchers’ (now graduate students) summer experience.